THESE QUALITIES OF THE POET WERE MANIFESTED - Boyxurozov Diyorbek Sherzod ugli (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation. The entire work of Maqsud Shaykhzoda is full of a deep political publicistic spirit. His poetic, dramatic works are in harmony with the times, no matter what theme they are devoted to. Therefore, the direct service of a creator of this type in  the  genre  of  journalism.  Well,  you  know,  increased  means  light,  light,  clarity. Indeed, our intelligentsia was called upon to do the best of knowledge, enlightenment, culture,  education..."With  this  word,  it  was  as  if  those  who  were  sitting  in  the Enchanted Assembly Hall had a thunderous applause.